Optimization of overliming detoxification of sugarcane bagasse hydrolysate by using response surface methodology for bio-ethanol production - Promta, Techut; Panomtian Thonkamdee; Kittikorn Sasujit (Maejo International Journal of Energy and Environmental Communication, 2024)
This research aimed to study of the sugarcane bagasse was used as a raw material for ethanol production and pretreatment with 2.0% dilute H2SO4 at 121oC for 60 min. Pichia stipitis (TISTR 5806) was a microorganism for fermentation. However, acid hydrolysis produces inhibitory compounds like furans, phenolics, and organic acids. Overliming with Ca(OH)2 is a detoxification process that removes these compounds and improves ethanol fermentation. Optimal conditions were determined using RSM and CCD frameworks. The study established specific ranges for the operation conditions: 7–12 for pH, 20–60oC for reaction temperature, and 30–90 min for reaction time. The results indicated that the optimal conditions for detoxification were a pH of 9.5, a reaction temperature of 40oC, and a reaction time of 60 min. The analysis revealed the removal of total furans at 38.37% and total phenolics at 50.02%. The fermentation of hydrolysate and detoxified hydrolysate found an ethanol yield of 0.22 and 0.30 gproduct/gsubstrate, respectively, and a theoretical yield of 43.42% and 57.96%, respectively. Overliming Ca(OH)2 could be an efficient detoxification process for removing and reducing the effects of inhibitory compounds in sugarcane bagasse hydrolysate.